Tourism Hospitality in Mandeh Tourism Development in Pesisir Selatan Regency, WestSumatra - Rifdatul Husna; Maya Permata Sari; Mega Dwi Septivani (International ABEC, 2022)
This study aims to analyze tourism services in developing Mandeh Tourism in Pesisir Selatan Regency, West Sumatra Province. Data were collected from 5 interviewed data sources and 93 respondents using a questionnaire. The research method uses qualitative methods as the main method and is supported by quantitative data. Based on this research, an analysis of tourism services in developing tourism is seen from the elements of Hospitality: Community hospitality, communication style, community culture, and events formedby Disparbud. By doing a SWOT analysis to find out what has the potential for tourism services in developing Mandeh Tourism objects in Pesisir Selatan Regency.